Very early endothelial cell loss after penetrating keratoplasty with organ-cultured corneas. Issue 8 (13th December 2016) - Gauthier, Anne Sophie; Garcin, Thibaud; Thuret, Gilles; He, Zhiguo; Jullienne, Remy; Trone, Marie Caroline; Nefzaoui, Chaker; Acquart, Sophie; Forest, Fabien; Péoc'h, Michel; Delbosc, Bernard; Gain, Philippe
Abstract : Aims: After keratoplasty, postoperative endothelial cell loss is calculated between the eye bank endothelial cell density (ebECD) and the postoperative specular microscopy (SM). To elucidate the very early cell loss, always described after penetrating keratoplasty (PK), we designed two complementary studies. Methods: (1) Clinical prospective study of 90 consecutive PKs (keratoconus, Fuchs' corneal dystrophy, lattice dystrophy, bullous keratopathy) with organ-cultured corneas and postoperative follow-up by SM at day 5 (D5), D15, month 1 (M1) and M3. This series provided a quantification of the difference between ebECD performed 2 days before graft and very early postoperative ECD. (2) Ten pairs of corneas with comparable ebECD in both corneas and same organ-culture (OC) duration were randomised: one cornea was grafted, and, at the same time, the viable ECD (vECD) of the other was measured after labelling with Hoechst/ethidium/calcein-AM. The relationship between vECD and very early postoperative ECD was studied. Results: vECD at the time of graft did not differ from ECD 5 days after PK, with a difference of 39 (−356; 355) cells/mm 2 (median (10°; 90° percentile, p=0.799)), whereas a significant difference of 755 (359; 1146) cells/mm 2, corresponding to 28% (95% CI 26 to 30) of cells, was measured between ebECD and ECD 5 days after PK (p<0.001). Conclusions: In OC, ebECD provided to surgeons significantly overestimate the number of viable ECs grafted to patients. The absence of difference between the vECD at D0 and ECD at D5 indicates that the very early endothelial cell loss is almost negligible in recipients.